Quantitative analysis of bioactive compounds in the aqueous extract of Ribes Diacanthum pall. - Batchuluun, Bujinlkham; Battulga, Sugarmaa; Ryenchindorj, Lkhaasuren; Davaasuren, Nyamdolgor; Tilyek, Akhtolkhyn; Luvsan, Khurelbaatar (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
Over the past 30 years, herbal medicines have been used globally, with over 80% of people turning to plant-based remedies for health-related needs. Ribes diacanthum Pall., known in Mongolia as “Tekhiin Sheeg,” is a shrub belonging to the Saxifragaceae family and commonly found in rocky mountain slopes, river valleys, and sand-rich areas near willow and poplar groves. In traditional Mongolian medicine, the aerial parts of this plant are used as a Aqueous extract to treat kidney and urinary tract inflammations, retention, and swelling. This quantifies specific bioactive compounds in the aqueous extracts prepared from different parts of Ribes diacanthum Pall., including the aerial parts. Aqueous extracts were obtained from the fruit (Sample 1), leaves (Sample 2), and stems (Sample 3) of Ribes diacanthum Pall using partial maceration. Total flavonoid and total phenolic contents in each sample were measured using spectrophotometry. The highest total flavonoid content was found in Sample 1 at 0.0032 ± 0.00058%, while the highest total phenolic content was in Sample 1 at 0.059 ± 0.0047%. Our study reveals that the aerial parts contain the highest total f lavonoid concentration, while the fruit has the highest total phenolic concentration, indicating their potential as valuable medicinal components.